A resource-based perspective on the relationship between service diversification and firm performance: evidence from Italian facility management firms - Giachetti, Claudio (Journal of Business Economics and Management, 2012)
In this article, a theoretical framework to study the effect of service diversification on firm financial performance is demonstrated. Data on 48 Italian facility management firms from between 2000 and 2009 show a consistent inverse U-shaped relationship between service diversification and firm performance, with the slope positive at low and moderate levels of service diversification but negative at high levels of service diversification. Further, the results show that firm experience in the service industry and firm affiliation to a consortium positively moderate the relationship between service diversification and performance. The results of this study provide evidence of the importance of service diversification strategies for gaining a competitive advantage.